Numerical simulation of December rainfall distribution in Mindanao using Mesoscale Model (MM5) - SAMUEL, DURAN (Archīum Ateneo, 2013)
The present study simulates the rainfall distribution for December 2002 and 2005 in Mindanao using mesoscale model (MM5). Sensitivity experiments are conducted to determine the best configuration of the model with respect to planetary boundary layer (PBL)